MODEL PENERAPAN ASPIRASI MASYARAKAT OLEH DEWAN PERWAKILAN RAKYAT DAERAH - Adianto '; Hasim As’ari (Universitas Riau, 2016)
Application Model Aspirations by the Regional Representatives Council. This study aims to determine the model of society by the application of the aspirations of the Regional Representatives Council (DPRD) at the Meranti Islands District. The informants are the chairman, deputy chairman and commissions in DPRD Meranti. Besides taken also from the media, civil society organizations, community leaders, youth leaders and education leaders in the District Meranti. Data collection technique was interview and observation. The data analysis is qualitative model from data collection, presentation of data, data reduction and conclusion. The results showed that the application of the aspirations of the people who do legislators Meranti district has been running well, although there are still people’s aspirations have not been followed up.